Labor Income in DIY During The Covid-19 Pandemic - Mustofa Mustofa (Ridwan Institute, 2022)
This article discusses workers' income in the Special Region of Yogyakarta (DIY) during the covid-19 pandemic. The data source used by Sakernas DIY for the August 2021 period with a selected sample of 4,029 workers. The analysis technique used is a regression analysis technique. The results showed that labour income during the Covid-19 period was influenced by education level, work experience, gender, marital status, job training, number of hours worked, digital devices, and work status, with a total effect of 40.5%. Workers with higher levels of education have better earnings. Workers who are equipped with job training have higher earnings. The number of hours affects income positively and significantly. Workers who use digital devices have higher incomes. Self-employment has a negative influence on income during a pandemic.